2017
DOI: 10.1038/s41467-017-00195-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic components embedded in a single graphene nanoribbon

Abstract: The use of graphene in electronic devices requires a band gap, which can be achieved by creating nanostructures such as graphene nanoribbons. A wide variety of atomically precise graphene nanoribbons can be prepared through on-surface synthesis, bringing the concept of graphene nanoribbon electronics closer to reality. For future applications it is beneficial to integrate contacts and more functionality directly into single ribbons by using heterostructures. Here, we use the on-surface synthesis approach to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
147
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 38 publications
7
147
0
Order By: Relevance
“…ZGNRs [26]). Eventually, embedding more functionality into the single GNRs through heterostructures [30,31,146] or topological properties [86,87] should allow the realization of more complex GNR devices. In the case of artificial lattices, practical applications are further into the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ZGNRs [26]). Eventually, embedding more functionality into the single GNRs through heterostructures [30,31,146] or topological properties [86,87] should allow the realization of more complex GNR devices. In the case of artificial lattices, practical applications are further into the future.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing nearly metallic GNR segments with wider band gap regions allows the realization of structures resembling a tunneling barrier with metallic leads (Fig. 6c) [146]. Since ultranarrow 5-AGNRs are nearly metallic [32], metal-semiconductor junctions can be achieved four monomer unit long 7-AGNR segment works effectively as a tunnel barrier between nearly metallic 5-AGNR leads (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The new device designed with multiple segments exhibits qualitatively better NDR characteristics and reasonable absolute current. [17,41,43] However, due to heightdependent variations of the sample-substrate coupling, [44] the band alignment in the HS can change in the lift-up configuration. It is found that the NDR feature of the 5-part structure is highly tolerant of variations in the segment widths.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] The recent development of graphene and graphene nanoribbons (GNRs) offers new opportunities to design nanoscale devices and to test NDR at the atomic scale. [15][16][17][18][19][20][21][22][23] In particular, controllable polymer-to-GNR conversion reaction was demonstrated using charge injection from a scanning tunneling microscope (STM) tip. [15][16][17][18][19][20][21][22][23] In particular, controllable polymer-to-GNR conversion reaction was demonstrated using charge injection from a scanning tunneling microscope (STM) tip.…”
Section: Introductionmentioning
confidence: 99%